MINIMIZING STUDENTSâ€™ ERRORS ON ANSWERING â€œYES/NOâ€ QUESTIONS ON READING COMPREHENSION - Kamarudin, Kamarudin (Jurnal Ilmiah IKIP Mataram, 2018)
This study is aimed at finding out the ways to minimize studentsâ€™ error and factors encountered by the students on answering â€œyes/noâ€ questions in reading comprehension at the first year students of SMPN 1 Sekotong. The number of population was 32 which were divided into 2 classes. The writer took 32 % of the students as the sample of the study or all of them. They were taken randomly as the sampling techniques to gain the data needed. The writer contributed a set of questionnaire which is consisted of 11 questions. The best ways to minimizing studentsâ€™ error on answering â€œyes/noâ€ questions in reading comprehension at the first year students of SMPN 1 Sekotong were Direct reference (45,7%) is very motivating, inference (37,1%) is fairly motivating, Supposition (42.9%) is motivating, Evaluation (37. 3%) is motivating. Some factors encountered by the students in answering â€œyes/noâ€ questions in reading comprehension at the first year students of SMPN 1 Sekotong were Language transfer (22.9 %) is motivating factors by the respondents Intra lingual interference (28, 6%) is not motivating factors of respondents, The sociolinguistics situation (35.7%) is fairly motivating factors of the respondents, Age (31.4%) motivating factors of respondents, Modality (22, 9 %) is poorly motivating factor, Succession of approximate system (37.3%) is not motivating factors of the respondents, Universal hierarchy of difficulty (37.1%) not motivating factors of respondents. The methods of teaching and learning process in the class support in minimizing studentsâ€™ error in answering â€œyes/noâ€ questions very well.